Verification of a HC-PK-CFD coupled program based a benchmark on beam trip transients for XADS reactor. (November 2019) - Gu, Zhixing; Li, Fei; Ge, Liangquan; Zeng, Guoqiang; Zhang, Qingxian; Shi, Jialei
Highlights: A transient analysis program HC-PK-CFD is developed. Verification of HC-PK-CFD is performed based on a benchmark on the beam trip transients for XADS reactor. It is demonstrated that the HC-PK-CFD program is capable and of enough accuracy to perform thermal-hydraulics/safety analysis problems. Abstract: It is important to employ multi-physics coupling strategy in thermal-hydraulics/safety analysis of nuclear reactors. In general, it is based on couplings of system codes with neutron dynamics codes, which is incompetent to cope with multi-dimensional thermal-hydraulics/safety problems involved in liquid metal cooled pool-type reactors. To cope with it, Computational Fluid Dynamics tools are good choices which have attracted considerable attentions in reactor simulation these years. In order to apply a commercial CFD program in thermal-hydraulics/safety analyses, the research on couplings of Point Kinetics (PK) model and a fuel pin Heat Conduction (HC) model to the commercial CFD platform FLUENT abbreviated as HC-PK-CFD is performed in this study. Verifications are performed by the benchmark simulation on beam interruption transients for an accelerator-driven sub-critical reactor system. It is demonstrated that the results simulated by HC-PK-CFD agrees well with the ones by other ten multi-physics coupling codes participating in this benchmark.